The Relationship Between Spin Crossover (SCO) Behaviors, Cation and Ligand Motions, and Intermolecular Interactions in a Series of Anionic SCO Fe(III) Complexes with Halogen-Substituted Azobisphenolate Ligands - Mai Hirota; Suguru Murata; Takahiro Sakurai; Hitoshi Ohta; Kazuyuki Takahashi (Molecules, 2024)
To investigate the halogen substitution effect on the anionic spin crossover (SCO) complexes, azobisphenolate ligands with 5,5′-dihalogen substituents from fluorine to iodine were synthesized, and their anionic FeIII complexes 1F, 1Cl, 1Br, and 1I were isolated. The temperature dependence of magnetic susceptibility and crystal structure revealed that 1F, 1Cl, and 1Br are all isostructural and exhibit SCO with the rotational motion of the cation and ligands, whereas 1I shows incomplete SCO. Note that 1Cl and 1Br showed irreversible and reversible cooperative SCO transitions, respectively. Short intermolecular contacts between the FeIII complex anions were found despite Coulomb repulsions for all the complexes. The topological analysis of the electron density distributions revealed the existence of X···X halogen bonds, C–H···X, C–H···N, and C–H···O hydrogen bonds, and C–H···π interactions are evident. The dimensionality of intermolecular interactions is suggested to be responsible for the cooperative SCO transitions in 1Cl and 1Br, whereas the disorder due to the freezing of ligand rotations in 1Cl is revealed to inhibit the SCO cooperativity.